The practice of online assessment in an EFL context amidst COVID-19 pandemic: views from teachers - Nasim Ghanbari (SpringerOpen, 2021)
Abstract For many years, technology has been applied to improve the quality of language learning and teaching. However, the outbreak of COVID-19 pandemic accelerated the integration of technology in different language learning contexts. The sudden shift to online teaching faced educators with an array of challenges they had not experienced before. In particular, the teachers encountered many barriers with the online assessment of the students. To shed more light on what passed, following a qualitative mode of inquiry, the present study set out to find out how a group of 20 Iranian English language teachers at Persian Gulf University faced with the online assessment challenges posed by COVID-19. For this aim, the researchers conducted in-depth semi-structured retrospective interviews with the teachers at different times throughout the course. In addition, the teachers were asked to provide a narrative account of how they responded to the crisis. The analysis of the findings showed that after the shift to online assessment, the teachers initially faced with serious pedagogical, technical, administrative, and affective barriers, but as the course proceeded, they could adjust their practice with the new situation. However, the teachers recounted problems that still remained and negatively affected their practice. Overall, the study discusses that to improve the online assessment in the post-COVID-19 era several technological, pedagogical, and administrative measures should be taken into account. These would further improve the integration of the technology in the pedagogical context in the long run.